Poverty in old age - Bernhard Ebbinghaus; Kenneth E. Nelson; Rense Nieuwenhuis (Luxembourg Income Study (LIS), 2019)
While the financial sustainability of pension systems has been high on reform agendas, the adequacy of retirement incomes has only recently come into focus. This chapter analyses old-age poverty from a comparative and longitudinal perspective using repeated waves of cross-sectional micro-level income data from the Luxembourg Income Study (LIS). We focus on high-income OECD countries that experienced demographic ageing and substantial pension reforms since the mid-1980s, and analyse old age poverty in terms of relative income positions and purchasing capacity. Overall, there has been a secular trend towards a decline in old age poverty, which has converged towards the poverty rates observed in the working age population. However, since ongoing pension reforms in several countries have reduced public benefits, fostered prefunded savings, augmented the retirement age, and strengthened the link between contribution histories and old-age incomes, we identify population subgroups that have difficulties in gaining sufficient pension credits or savings into individual pension plans during their working lives to escape poverty in old age, including women, migrants, and those with lower education. We also present examples of poverty trends across synthetic cohorts in old age. Overall, we observe that more recent cohorts are better protected against poverty in old age compared to cohorts that were born longer ago.
Keywords: 330